Black Box Testing on Website-Based Guestbook Registration Applications - Salih , Yasir; Saefullah, Rifki (Communication In Research And Publications, 2024)
In the rapidly developing digital era, website-based applications have become an important means of meeting the needs of various uses. One application that has received attention is the guest book registration application, which aims to record and manage guest information efficiently. In this context, application testing becomes crucial to ensure service quality, security and availability. This research focuses on black box testing, a software testing method that emphasizes the functionality and reliability of applications from the user's perspective. Testing covers key aspects such as data input, and key functionality. Through this approach, it is hoped that the research results can contribute to the development of a website-based guestbook registration application that is more reliable and suits user needs.